Integrasi Big Data Dan Data Science Dalam Tata Kelola Keuangan Daerah: Pembelajaran Dari Kota Bandung - Muh Rivandi Setiawan (JEKP (Jurnal Ekonomi dan Keuangan Publik), 2025)
ABSTRACT Regional budget planning is a crucial pillar of public financial governance at the local level, yet it often faces uncertainty due to fluctuations in regional own-source revenue, changes in central fiscal policies, and non-linear spending dynamics. Inaccurate projections may lead to budget deficits, inefficient expenditures, or even public resource waste. This study aims to analyze the potential application of Data Science methods—particularly regression and time series forecasting—to develop predictive models capable of more accurately estimating revenue and expenditure realization for the Bandung City Government. Secondary data were collected from the Directorate General of Fiscal Balance (DJPK), Central Bureau of Statistics (BPS), and Bandung’s Open Data portal, covering historical Regional Revenue and Expenditure Budgets (APBD), budget realization records, macroeconomic indicators (such as inflation, economic growth, and unemployment rates), and demographic data. By analyzing historical patterns and identifying key determinants of budget performance, the model is designed to generate realistic projections and data-driven policy recommendations. Results indicate that the Data Science approach enhances budget planning precision, minimizes deviation risks, and supports more transparent and accountable decision-making. This research is expected to serve as a foundation for digital transformation in regional financial management, while also promoting budget efficiency and responsiveness to actual community needs. Ultimately, integrating predictive analytics into fiscal planning can strengthen governance, optimize resource allocation, and improve public service delivery at the local government level. Keywords: Data Science, budget prediction, regional finance, Bandung City, planning. ABSTRAK Perencanaan anggaran daerah merupakan pilar penting dalam tata kelola keuangan publik di tingkat lokal, namun seringkali dihadapkan pada ketidakpastian akibat fluktuasi pendapatan asli daerah, perubahan kebijakan fiskal pusat, serta dinamika belanja yang tidak selalu linier dengan rencana awal. Ketidakakuratan proyeksi dapat berdampak pada defisit anggaran, inefisiensi belanja, atau bahkan pemborosan sumber daya publik. Penelitian ini bertujuan menganalisis potensi penerapan metode Data Science—khususnya teknik regresi dan time series forecasting—untuk membangun model prediktif yang mampu memperkirakan realisasi pendapatan dan belanja Pemerintah Kota Bandung secara lebih akurat. Data sekunder dikumpulkan dari Direktorat Jenderal Perimbangan Keuangan (DJPK), Badan Pusat Statistik (BPS), dan portal Open Data Kota Bandung, mencakup APBD historis, realisasi anggaran, indikator ekonomi makro (seperti inflasi, pertumbuhan ekonomi, dan tingkat pengangguran), serta data demografi. Melalui analisis pola historis dan identifikasi variabel penentu kinerja anggaran, model ini dirancang untuk memberikan proyeksi realistis dan rekomendasi kebijakan berbasis data. Hasilnya menunjukkan bahwa pendekatan Data Science mampu meningkatkan presisi perencanaan anggaran, meminimalkan risiko deviasi, dan mendukung pengambilan keputusan yang lebih transparan dan akuntabel. Penelitian ini diharapkan menjadi dasar transformasi digital dalam pengelolaan keuangan daerah, sekaligus mendorong efisiensi dan responsivitas anggaran terhadap kebutuhan riil masyarakat. Kata kunci: Data Science, prediksi anggaran, keuangan daerah, Kota Bandung, perencanaan.